ABORSI DI PERSIMPANGAN HUKUM DAN AGAMA: Perspektif Politik Hukum Kesehatan dan Islam di Indonesia - Maulida Khairunnisa; Kefi Miftachul Ulum Kefi; Fahmi Makraja; Rodhotun Nimah (PT Taskuliah Edukasi Indonesia, 2024)
The majority of people consider abortion as an act of murder because the fetus in the mother's womb has the right to live. Pregnancy outside of marriage in Indonesia continues to increase every year, often resulting in unwanted children, including those resulting from rape. This condition often leads to unsafe abortion because the child is considered a burden. This study aims to explain the political view of health law on abortion in Indonesia as well as the Islamic perspective. This type of research is a literature study with a normative juridical approach. The research is descriptive-analytical by describing relevant concepts to be analyzed to produce conclusions. Data were collected through analysis of legislation such as the 1945 Constitution of the Republic of Indonesia, Law No. 17 of 2023 on Health, Government Regulation No. 61 of 2014 on Reproductive Health, and Government Regulation No. 28 of 2024 as the implementation of the Health Law, as well as secondary sources in the form of books, journals, and other scientific articles. The results show that the politics of health law is an effort by policymakers to protect women and their reproductive health through the regulation of safe, quality, and responsible abortion. The act of abortion is strictly regulated and can only be performed by qualified health personnel in cases of indications of medical emergencies or pregnancy due to rape that has the potential to cause psychological trauma. However, abortion without medical reasons remains prohibited, both in Indonesian positive law and in the perspective of Islamic law. In conclusion, the politics of health law in Indonesia has an important role to play in balancing the protection of women's health with legal constraints and religious values, although social and ethical challenges remain significant issues. [Mayoritas masyarakat menganggap aborsi sebagai tindakan pembunuhan karena janin dalam kandungan ibu memiliki hak untuk hidup. Kehamilan di luar perkawinan di Indonesia terus meningkat setiap tahunnya, sering kali menghasilkan anak yang tidak diinginkan, termasuk akibat pemerkosaan. Kondisi ini sering berujung pada aborsi tidak aman karena anak dianggap sebagai beban. Penelitian ini bertujuan untuk menjelaskan pandangan politik hukum kesehatan terhadap aborsi di Indonesia serta perspektif Islam. Jenis penelitian ini adalah studi kepustakaan dengan pendekatan yuridis normatif. Penelitian bersifat deskriptif-analitis dengan menggambarkan konsep-konsep yang relevan untuk dianalisis hingga menghasilkan kesimpulan. Data dikumpulkan melalui analisis peraturan perundang-undangan seperti Undang-Undang Dasar NRI 1945, Undang-Undang No. 17 Tahun 2023 tentang Kesehatan, PP No. 61 Tahun 2014 tentang Kesehatan Reproduksi, dan PP No. 28 Tahun 2024 sebagai pelaksanaan Undang-Undang Kesehatan, serta sumber sekunder berupa buku, jurnal, dan artikel ilmiah lainnya. Hasil penelitian menunjukkan bahwa politik hukum kesehatan adalah upaya para pembuat kebijakan untuk melindungi perempuan dan kesehatan reproduksinya melalui regulasi aborsi yang aman, bermutu, dan bertanggung jawab. Tindakan aborsi diatur secara ketat dan hanya dapat dilakukan oleh tenaga kesehatan yang memenuhi syarat dalam kasus indikasi kedaruratan medis atau kehamilan akibat perkosaan yang berpotensi menyebabkan trauma psikologis. Namun, aborsi tanpa alasan medis tetap dilarang, baik dalam hukum positif Indonesia maupun dalam perspektif hukum Islam. Kesimpulannya, politik hukum kesehatan di Indonesia memiliki peran penting dalam menyeimbangkan perlindungan kesehatan perempuan dengan batasan hukum dan nilai-nilai agama, meskipun tantangan sosial dan etis tetap menjadi isu yang signifikan].